2013 IEEE 59th Holm Conference on Electrical Contacts (Holm 2013) 2013
DOI: 10.1109/holm.2013.6651433
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Switching Lifetime of Chromium Adhesion Layers in Gold-Coated Electrical Contacts under Cold and Hot Switching Conditions

Abstract: -Gold is commonly used for electrical contacts due to its many desirable electrical and mechanical properties. Throughout the switch lifetime, the contacts are required to survive a large number of opening and closing cycles and therefore it is important to understand the failure mechanisms. Adhesion layers (e.g. chromium or titanium) can be deposited to increase the adhesion of the gold layer to the contact surface. In this work, the inclusion of a chromium adhesion layer shows an improvement of the switching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…silicon) [17]. The switching lifetime of thin-film Au-contacts with and without a Cr adhesion layer were measured under hotswitching conditions to evaluate the effect of the adhesion layer.…”
Section: Pzt Test Rig: Dry-switching Versus Hot-switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…silicon) [17]. The switching lifetime of thin-film Au-contacts with and without a Cr adhesion layer were measured under hotswitching conditions to evaluate the effect of the adhesion layer.…”
Section: Pzt Test Rig: Dry-switching Versus Hot-switchingmentioning
confidence: 99%
“…The switching lifetime of thin-film Au-contacts with and without a Cr adhesion layer were measured under hotswitching conditions to evaluate the effect of the adhesion layer. On the PZT rig, it was shown that failure between an Au-coated ball and an Au-coated substrate occurred at approximately 600,000 cycles planar when hot-switching with a load current of 50 mA (at 4 V) with 1 mN contact force [17]. The failure was identified by monitoring the contact resistance; upon failure the contact resistance increases significantly (i.e.…”
Section: Pzt Test Rig: Dry-switching Versus Hot-switchingmentioning
confidence: 99%
“…The final step is to sputter coat the cantilever beam with a 10 nm layer of chromium and a 500 nm layer of gold. The chromium layer is an adhesion layer to promote the adhesion of the gold to the silicon [11]. An image of the Au-coated cantilever beam is given in Figure 1b.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…[8][9][10] Studies of the Au/MWCNT composites compare to the more orthodox sputtered Au/Si as an electrical contact, showing the metal-CNT composite to have exceeded the lifetime of the orthodox contact by several orders of magnitude. [8][9][10] In this study, the results are used to evaluate the electromechanical properties of the samples by investigating the contact resistance of the composite under various loads by means of a modified nanoindenter and fitting to the Holm electrical contact model. Holm described the contact resistance of a pair of contacts in terms of the applied load, F, as…”
mentioning
confidence: 99%
“…The samples investigated were of the same structure as those tested for potential in MEMS switching applications, [8][9][10] consisting of a subsurface of MWCNTs sputter coated with a conductive Au film. In order to further investigate the potential applications of the composite, a series of samples with varying composition were fabricated for this study, these were composed of different thickness of Au film and lengths of MWCNTs.…”
mentioning
confidence: 99%